밭 토양에서 유기물 자원의 시용이 작물 수량 및 토양 물리성에 미치는 영향 - 한경화; Kyunghwa Han; 정강호; Kangho Jung; 조희래; Heerae Cho; 이협성; Hyubsung Lee; 옥정훈; Junghun Ok; 장용선; Yongseon Zhang; et al. (유기물자원화, 2017)
농경지에 유기물 자원을 시용하면 지력이 높아져서 작물의 수량이 높아진다. 본 연구의 목적은 유기물자원을 밭 토양에 시용하였을 때 작물 수량 및 토양 물리성에 미치는 영향을 유기물 자원별로 비교하고자 하였다. 콩을 평야지인 수원의 사양토와 식양토 포장에서 재배하였으며, 온도 영향을 살펴보기 위하여 고랭지 평창의 사양토 포장에서도 수행하였다. 시험에 쓰인 유기물 자원은 볏짚퇴비, 돈분톱밥퇴비, 계분톱밥퇴비, 코코피트였으며, 콩 파종 전에 탄소 기준으로 동등한 수준으로 시용하였다. 무기질비료의 시용량은 토양검정한 분석치를 고려하여 결정하였다. 유기물 자원의 분해 특성을 살펴보기 위하여 항온배양실험을 실내에서 사양토를 대상으로 수행하였다. 분해 속도는 볏짚퇴비가 가장 높았으며, 돈분톱밥퇴비, 코코피트 순이었다. 유기물자원의 시용에 따른 콩 수량의 증가 효과는 사양토에 비해서 식양토에서 높았다. 기상 비율의 증가 효과도 식양토에서 뚜렷하였다. 반면에 토양 입단 안정성의 증가 효과는 사양토에서 비교적 높았다. 볏짚퇴비가 모든 토양에서 콩 수량의 증가 효과가 가장 높았다. 코코피트의 콩 수량 증가 및 토양 물리성 개선 효과는 다른 유기물 자원에 비해서 높지 않았다. 따라서 밭작물 수량의 증대 및 토양 물리성의 개선을 위해서는 축분퇴비 등 다른 유기물 자원에 비해서 볏짚퇴비가 적합하였다. Application of organic resources to agricultural land can increase crop yield by improving soil characteristics. The objective of this study was to evaluate effect of crop yield and soil physical properties including aggregate stability to application of organic resources in upland. The soybean was cultivated in a sandy loam field and a clay loam field located at Suwon and a sandy loam field located at Pyeongchang. The organic resources used in this study were rice straw compost (RSC), composted pig manure with sawdust (CPIG), composted poultry manure with sawdust (CPM), and cocopeat applied before sowing crop. Application rate of organic resources was determined based on carbon content and water content. The inorganic fertilizers were applied based on soil testing. In addition, the decomposition of RSC, CPIG, and cocopeat was characterized by isothermal incubation with sandy loam soil. The decomposition rate was highest for RSC followed by CPIG and cocopeat. Organic resource application increased yield of soybean, which effect was greater in clay loam than in sandy loam. In addition, increase in gas phase proportion by organic resource application was distinct in clay loam soil compared with sandy loam soil. In terms of aggregate stability, increasing effect was more obvious in sandy loam soils than in a clay loam soil. The highest yield was observed in RSC treatment plots for all the fields. Improvement of soybean yield and soil physical characteristics by cocopeat was not as much as that of the other organic resources. The results implied that RSC could be recommended for promoting aggregate stability and crop yield in upland cultivation.